Влияние UVB – 311 Hм Фототерапии на биофизические свойства пораженной псориазом кожи = The influence of UVB – 311 nm phototherapy on biophysical properties of psoriatic skin - Bohatyrova, I. N. (Journal of Education, Health and Sport, 2015)
Bohatyrova I N. Влияние UVB – 311 Hм Фототерапии на биофизические свойства пораженной псориазом кожи = The influence of UVB – 311 nm phototherapy on biophysical properties of psoriatic skin. Journal of Education, Health and Sport. 2015;5(5):363-367. ISSN 2391-8306. DOI 10.5281/zenodo.17883 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A363-367 https://pbn.nauka.gov.pl/works/561487 http://dx.doi.org/10.5281/zenodo.17883 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 20.05.2015. УДК 616.5:616.838.03 ВЛИЯНИЕ UVB – 311Hм ФОТОТЕРАПИИ НА БИОФИЗИЧЕСКИЕ СВОЙСТВА ПОРАЖЕННОЙ ПСОРИАЗОМ КОЖИ The INFLUENCE of UVB – 311nm PHOTOTHERAPY ON BIOPHYSICAL properties of PSORIATIC SKIN И. Н.Богатырева I N Bohatyrova Донецкий национальный медицинский университет им. М.Горького Donetsk National Medical University Summary. In order to evaluate the effect of narrowband UVB phototherapy on the biophysical properties of the skin were studied indicators of hydration and pH affected and unaffected in 30 patients with plaque psoriasis before and after treatment. The control group consisted of 10 people aged representative without pathology of the skin. All psoriasis patients showed reductions in skin hydration, pH changes, as in the lesions and on the same skin. It is shown that in the process of UVB phototherapy, along with regression of clinical manifestations dermatosis and recovery biophysical skin properties, even at the last settings unchanged skin not reach values of the control group. The expediency of application of moisturizers in the process of remission of dermatosis. Keywords: psoriasis, narrowband phototherapy, biophysical properties of the skin. ВПЛИВ UVB – 311Нм ФОТОТЕРАПІЇ НА БІОФІЗИЧНІ ВЛАСТИВОСТІ УРАЖЕНОЇ ПСОРІАЗОМ ШКІРИ. З метою оцінки впливу вузькосмугової UVB фототерапії на біофізичні властивості шкіри досліджені показники гідратації, вискоеластичності і рН ураженої і неураженої у 30 хворих бляшковим псоріазом до- і після лікування. Контрольну групу склали 10 чоловік репрезентативного віку без патології шкіри. В усих хворих псоріазом виявлено зниження показників гідратації і вискоеластичності шкіри, зміни рН, як в осередках ураження, так і на незмінній шкірі. Показано, що в процесі UVB фототерапії, разом з регресом клінічних проявів дерматозу і відновленням біофізичних властивостей шкіри, параметри останніх навіть на незмінній шкірі не досягають значень контрольної групи. Обгрунтована доцільність застосування зволожуючих засобів в процесі ремісії дерматозу. Ключові слова: псоріаз, вузькосмугова фототерапія, біофізичні властивості шкіри. Резюме. С целью оценки влияния узкополосной UVB фототерапии на биофизические свойства кожи исследованы показатели гидратации, вискоэластичности и рН пораженной и непораженной у 30 больных бляшечным псориазом до- и после лечения. Контрольную группу составили 10 человек репрезентативного возраста без патологии кожи. У всех больных псориазом выявлено снижение показателей гидратации и вискоэластичности кожи, изменения рН, как в очагах поражения, так и на неизменной коже. Показано, что в процессе UVB фототерапии, наряду с регрессом клинических проявлений дерматоза и восстановлением биофизических свойств кожи, параметры последних даже на неизменной коже де достигают значений контрольной группы. Обоснована целесообразность применения увлажняющих средств в процессе ремиссии дерматоза. Ключевые слова: псориаз, узкополосная фототерапия, биофизические свойства кожи.